(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Antibiotic-resistant microorganisms constitute one of the gravest threats to contemporary global public health, responsible for 1.27 million attributable deaths annually. This article examines the epidemiological burden of antimicrobial resistance, resistance transmission mechanisms, the clinical significance of ESKAPE pathogens in nosocomial settings, and evidence-based infection control and antibiotic stewardship strategies applicable to Central Asian healthcare institutions.